Readability of Instructional Materials and Usability of Online Learning Environment: Their Relations to the Development of Authentic and Contingent Knowledge - Lisa Casper; Jeanne M. Myers; Chris L. Yuen (Adult Education Research Conference, 2015)
This research project correlates authentic knowledge with the readability of instructional materials and contingent knowledge with usability of the online learning environment. Based on thematic analyses in above two areas, we propose a model that governs how adult learners develop authentic and contingent knowledge in an intertwined manner.
Keywords: online learning environment; usability; readability; integral theory